Política industrial, la experiência boliviana - Gamarra, Roberto del Barco (Ciência & Trópico, 2013)
ABSTRACT This proposal analyzes the importance of industrial policy– which in general terms was defined by Dani Rodrik as an interactive process of strategic cooperation between the public and private sectors – and its linkage with the State to reduce productivity gaps and improve cohesion between productive agents. On the other hand, the lessons of the three member countries of “the rest,” following the group definition of Alice Amsden, allow adequate space to open a debate about the necessity of a developmentalist state – a promoter and driver of industrial policy – that boosts diversification of the productive matrix, acting against the postulates of “comparative advantage.” Following this, it describes the balance of industrial policy in Bolivia, putting emphasis on the mining sector, finishing with a description of the failed experience of Bolivian lithium exploitation at the end of the last century. KEYWORDS: Development. Developmentalist State. Industrial Policy. Bolivian Mining Policy. RESUMO Esta proposta analisa a importância da política industrial que, em termos gerais, foi definida por Dani Rodrik como um processo interativo de cooperação estratégica entre os setores público e privado – e sua articulação com o Estado para reduzir as diferenças de produtividade e melhorar a coesão entre os agentes produtivos. Por outro lado, as lições dos três países membros, segundo a definição do grupo de Alice Amsden, deixam espaço suficiente para abrir um debate sobre a necessidade de um Estado desenvolvimentista – um promotor e controlador da política industrial – que impulsiona a diversificação da matriz produtiva, agindo contra os postulados da “vantagem comparativa”. Após isso, há a descrição do balanço da política industrial, na Bolívia, com ênfase no setor de mineração, terminando com uma descrição da experiência fracassada de exploração de lítio boliviano no final do século passado. PALAVRAS-CHAVE: Desenvolvimento. Estado desenvolvimentista. Política Industrial. Bolívia política de mineração